Resolution of the Main Values of Wasathiyah Islam as an Effort to Counter the Movement of Religious Radicalism - Azisi, Ali Mursyid; Faiz, Muhammad Taqiyuddin Iqbal; Permatasari, Novia Maharani; Zidni, Abdullah; Muttaqin, Ittihaf Siddatul (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2023)
This article specifically examines the resolution of the core values of wasathiyah Islam as an effort to counter the movement of religious radicalism, both directly in the community and in the digital space. Wasathiyah Islam as a form of rahmatan lil 'alamin is an understanding that needs to be disseminated in order to achieve harmony, security, and peace in religion. This article uses a qualitative method of descriptive analysis with library research steps sourced from books, journals, and other supporting data. The article argues that the nature of the value of wasathiyah Islam that consists of: Rahamutiyah (the flow and outpouring of affection without limitation, without discrimination and without pause), Insaniyah (humanity), 'Adliyyah (fairness), Mubadalah (equality), Maslahah (benefit), Mu'ahadah Wathaniyah (maintaining national ties), Dusturiyah (obeying the rules that have been agreed upon, for example the laws that apply in a country), Tasamuh (tolerance), and 'Urfiyah (not rejecting customs/traditions, and can even make them a component of the source of law) needs to be encouraged in various spaces of life, including on the internet. That way, the future of Indonesian Muslims will be protected from exposure to religious radicalism.